2011
DOI: 10.1111/j.1365-2710.2011.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytochrome P450 3A4 inhibitor ketoconazole on risperidone pharmacokinetics in healthy volunteers

Abstract: The pharmacokinetics of risperidone was affected by the concomitant administration of ketoconazole. If a CYP3A4 inhibitor is used concomitantly with risperidone, it is necessary for the clinicians to monitor their patients for signs of adverse drug reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Studies in a more diverse patient population, which would include patients receiving chronic therapy and especially with PMs of CYP2D6, may allow a more meaningful examination of the influence of CYP2D6 on risperidone disposition. Besides, it was expected that the other enzymes including CYP3A4/5 might have influence on the metabolism of risperidone as seen from drug interaction studies with ketoconazole [44] and rifampin [45]. This study would provide comparative information on the metabolic index between Korean and other ethnic groups, and this information would be useful in establishing criteria for phenotype/genotype correlation in the future study.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in a more diverse patient population, which would include patients receiving chronic therapy and especially with PMs of CYP2D6, may allow a more meaningful examination of the influence of CYP2D6 on risperidone disposition. Besides, it was expected that the other enzymes including CYP3A4/5 might have influence on the metabolism of risperidone as seen from drug interaction studies with ketoconazole [44] and rifampin [45]. This study would provide comparative information on the metabolic index between Korean and other ethnic groups, and this information would be useful in establishing criteria for phenotype/genotype correlation in the future study.…”
Section: Discussionmentioning
confidence: 97%
“…CYP3A4 is abundant in human liver microsomes and plays an important role in the metabolism of many drugs, including anticancer drugs. Furthermore, CYP3A4 shows about five-to tenfold inter-patient variability [25][26][27] in the disposition of these drugs metabolic efficiency, and intra-patient variability is widely recognized for several major inducers [28,29] or inhibitors [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CYP3A4 by ketoconazole has been shown to result in increased plasma concentrations or decreased clearance of several atypical antipsychotics, including clozapine, quetiapine, ziprasidone, and risperidone [19][20][21]. Studies in healthy volunteers have shown that rifampin decreases plasma concentrations and increases clearance of risperidone [22,23], and there is evidence implicating rifampin in a clinically significant interaction with clozapine [24].…”
Section: Discussionmentioning
confidence: 99%